2013
DOI: 10.1002/pbc.24678
|View full text |Cite
|
Sign up to set email alerts
|

Distal ulnar changes in children with thalassemia and deferiprone related arthropathy

Abstract: Bony dysplasia, deformation and impaired growth of ulnar epiphyses, metaphyses and physes may be an expression of deferiprone related arthropathy in children with thalassemia major.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Arthropathy of large joints has been recognized as a toxic side effect of deferiprone (DFP) therapy. Bilateral knee involvement is most common, but ankles, hips, shoulders, elbows, wrists and small joints of the hands and feet can also be affected [65][66][67][68][69] . Clinically, the patients complain for musculoskeletal stiffness, joint pain, swelling and effusion, more frequently involving the knees 70 .…”
Section: Deferiprone Related Arthropathymentioning
confidence: 99%
“…Arthropathy of large joints has been recognized as a toxic side effect of deferiprone (DFP) therapy. Bilateral knee involvement is most common, but ankles, hips, shoulders, elbows, wrists and small joints of the hands and feet can also be affected [65][66][67][68][69] . Clinically, the patients complain for musculoskeletal stiffness, joint pain, swelling and effusion, more frequently involving the knees 70 .…”
Section: Deferiprone Related Arthropathymentioning
confidence: 99%
“…Sharma et al reported similar radiological features in their study. 24,25 Radiological changes in thalassemia are usually evident by 1 year of age, these changes do occur at an earlier age with severe form in under transfused or non-transfused thalassemic children. Radiological changes are due to ineffective erythropoiesis, anaemia and hypoxia resulting in increased erythropoietin.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies observed that arthropathy is more common in patients with high serum ferritin and DFP doses above 100 mg/kg/d (33,42,54,95), but this could not be confirmed by another study (43). Suspected long-term effects of DFP-related arthropathies are bony dysplasia, deformation and impaired growth of ulnar epiphyses, metaphyses and physes (102).…”
Section: Deferiprone (Dfp)mentioning
confidence: 98%